Morphological Characterization of Arum cyrenaicum Hruby Plant in Al-Jabal Al-Akhdar Region - Libya - Ahmed Amrajaa Abdulrraziq; Sami Mohammed Salih (مجلة المختار للعلوم, 2020)
: The Araceae family is one of the widely distributed plant families globally and among the native species representing this family in Libya, especially in Al-Jabal Al-Akhdar region, is Arum cyrenaicum. which has not been studied morphologically since 1977. Therefore, this study aims to give a detailed morphological characterization of Arum cyrenaicum. and verify that there are no other species of Arum in nineteen locations of Al-Jabal Al-Akhdar for two seasons 2019-2020, and as a study to be added to the Libyan flora data. The results of the field study showed the presence of Arum cyrenaicum. in all studied locations. The study was also able to record it for the first time at 14 new locations and did not record any other genus Arum species. The results of the morphological study also showed that it is a tuber discoid herbaceous annual plant, which grows in the early fall season. It is characterized by simple sagittate and hastate leaves with long petiole, single inflorescence (spadix), sail shaped, dark purple in color, and it consists of two parts (spathe, spadix). It has the smell of dung, is bisexual, monoecious, with female flowers situated at the bottom of male flowers, anther consistes of two thecae, superior ovary with single locule, parietal placentation, fruit berries red when ripe, and a seed shape ovate.